Association between thyroid hormone and cardiovascular health: A cross-sectional study - Tongtong Bai; Juanjuan Peng; Chengyu Wu; Tonghua Liu (PLoS ONE, 2025)
Background Large-sample clinical research evidence in humans regarding the association between thyroid hormones and cardiovascular health is limited. The American Heart Association introduced the Life’s Essential 8 (LE8) as a novel metric for assessing cardiovascular health. This study aimed to explore the plausible connection between thyroid hormone levels and LE8. Methods This study employed data extracted from the National Health and Nutrition Examination Survey spanning from 2007–2012, focusing on individuals aged 20 and above. To investigate the association between thyroid hormone and LE8, diverse analytical methods, including weighted multivariate linear regression, restricted cubic spline curves, and stratified analysis, were utilized. Results A total of 3,019 participants were enrolled in this study. The highest LE8 score group (≥ 80) comprised 610 participants (20.21%). In the fully adjusted linear regression analysis, elevated levels of ln(FT3), ln(TT3), and ln(Tg) were significantly associated with a reduced level of LE8 ( β (95% Confidence Interval): −6.31 (−12.13, −0.49), p = 0.035; −5.18 (−8.22, −2.15), p = 0.002; −0.98 (−1.74, −0.22), p = 0.014). The analysis revealed nonlinear relationships between ln(Tg), ln(TgAb), ln(TPOAb), and LE8. In the group with normal thyroid hormone levels, ln(TT3), ln(TT4), and ln(Tg) correlated with LE8 in the stratified analysis. Conclusion Alterations in FT3, TT3, TT4, Tg, TgAb, and TPOAb levels correlated with variations in LE8. Adherence to cardiovascular health recommendations may be pertinent to the preservation of thyroid health.